Volatility transmission across financial markets: A semiparametric analysis - Theoplasti Kolaiti; Mwasi Mboya; Philipp Sibbertsen (Journal of Risk and Financial Management, 2020)
This paper revisits the question whether volatilities of different markets and trading zones have a long-run equilibrium in the sense that they are fractionally cointegrated. We consider the U.S., Japanese and German stock, bond and foreign exchange markets to see whether there is fractional cointegration between the markets in one trading zone or for one market across trading zones. Also the other combinations of different markets in different trading zones are considered. Applying a purely semiparametric approach through the whole analysis shows fractional cointegration can only be found for a small minority of different cases. Investigating further we find that all volatility series show persistence breaks during the observation period which may be a reason for different findings in previous studies.
Keywords: C14; C32; G15; 330; fractional cointegration; high-frequency data; realized volatility; semiparametric estimation